Assessing the Validity of Emotional Intelligence Measures. (January 2018) - Miners, Christopher T. H.; Côté, Stéphane; Lievens, Filip
We describe an approach that enables a more complete evaluation of the validity of emotional intelligence measures. We argue that a source of evidence for validity is often overlooked by researchers and test developers, namely, evidence based on response processes. This evidence can be obtained through (a) a definition of the ability, (b) a description of the mental processes that operate when a person uses the ability, (c) the development of a theory of response behaviour that links variation in the construct with variation on the responses to the items of a measure, and (d) a test of the theory of response behaviour through one or more strategies that we describe.